Development of a high particle loading novel copper ink for the fabrication of a three-dimensional hierarchical porous structure using direct ink writing and sintering - Tripathi V.M.; Sharma P.; Tyagi R. (My University, 2025)
Recently, the direct ink writing (DIW) of hierarchical porous copper (Cu) (HP-Cu) for lithium metal battery applications has attracted significant attention. To achieve this, Cu ink with ideal rheological properties and high particle loading is necessary. However, to date, no work focusing on systematic Cu ink development with Cu particle loading more than 95 wt% has been reported. Hence, in the present work, a novel Cu ink with a particle loading of more than 95 wt%, and polylactic acid (PLA) as a binder has been developed. The rheological behavior of the Cu ink with different amounts of Cu loading i.e. 93, 95 and 97 wt% respectively were investigated. Moreover, the modelling using the Herschel-Bulkey equation was done to establish the rheology. All the prepared inks showed viscoelastic and shear thinning behaviour. Moreover, the ink having 97wt%Cu loading exhibited optimum rheology with a shear elastic modulus of around 105Pa in the linear viscoelastic area. Subsequently, DIW using the prepared Cu inks followed by sintering was performed. The morphological study of the 3D printed Cu green samples and sintered samples was performed and it was found that the variation in Cu particle loading significantly affected the density and volumetric shrinkage. Finally, an HP-Cu sample having a pore size less than 200 μm was fabricated using DIW and sintering to validate the efficacy of the developed Cu ink. Proper interparticle bonding between the Cu particles was observed indicating that the developed ink is suitable for the fabrication of complex Cu parts for lithium metal battery application. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.